2011
DOI: 10.1039/c1dt10908a
|View full text |Cite
|
Sign up to set email alerts
|

Control of the transition temperatures of metallomesogens by specific interface design: application to Mn12 single molecule magnets

Abstract: Reaction of the Single Molecule Magnet [Mn(12)O(12)(CH(3)CO(2))(16)(H(2)O)(4)] (Mn(12)) with mesogenic dendritic ligands Li (i = 4, 5) quantitatively yields functional clusters [Mn(12)O(12)(Li-H)(16)(H(2)O)(4)] (i = 4, 5) that self-organize into a thermotropic SmA-type liquid crystalline phase. The perturbation of the molecular interface by methylation of the terminal mesogenic cyanobiphenyl groups induces a significant decrease of the clearing temperature without affecting the magnetic properties and the supr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…When these metallic blocks are much larger than the mean size of the mesogenic part, mesomorphism can even be suppressed. However, their incorporation into LC phases has been successfully achieved through the use of voluminous mesomorphic dendritic systems, 12 and beautiful examples of LC catenanes 13 and rotaxanes 14 among other systems 15,16 can be found in the literature. Herein, we report the synthesis, properties, and supramolecular organization of the first members of a new family of liquid-crystalline host−guest complexes based on an organometallic Ru 4 cage (host) and liquid-crystalline dendrimers (guests).…”
Section: ■ Introductionmentioning
confidence: 99%
“…When these metallic blocks are much larger than the mean size of the mesogenic part, mesomorphism can even be suppressed. However, their incorporation into LC phases has been successfully achieved through the use of voluminous mesomorphic dendritic systems, 12 and beautiful examples of LC catenanes 13 and rotaxanes 14 among other systems 15,16 can be found in the literature. Herein, we report the synthesis, properties, and supramolecular organization of the first members of a new family of liquid-crystalline host−guest complexes based on an organometallic Ru 4 cage (host) and liquid-crystalline dendrimers (guests).…”
Section: ■ Introductionmentioning
confidence: 99%
“…an intra-layer order associated with a specic arrangement of the strongly diffraction inorganic cores. 56,57 Below 0.5, however, the diffraction patterns are signicantly different, the relative broadness of the diffractions and the disappeared 001 reection suggest that SEP-1 is dispersed throughout the P4VP 571 polymer matrix and is not able to condense and self-assemble into successively ordered domains any more.…”
Section: The Characterization Of Hydrogen-bonding Formation Between P...mentioning
confidence: 99%
“…DSC measurements showed that the resultant macromolecules were thermally unstable, and decomposed before the clearing point. In subsequent work, the authors focused on reducing the clearing temperatures through adding a side methyl group to the cyanobiphenyl unit . Thermal analysis revealed that the steric hindrance of the side group can perturb the molecular packing and reduce the clearing temperature.…”
Section: Thermotropic Lcs Based On Coordination Bondsmentioning
confidence: 99%
“…In subsequent work, the authors focused on reducing the clearing temperatures through adding a side methyl group to the cyanobiphenyl unit. 76 Thermal analysis revealed that the steric hindrance of the side group can perturb the molecular packing and reduce the clearing temperature. Significantly, the LC macromolecules retained the magnetic properties of the single-molecule magnets, providing the potential for the fabrication of macroscopic magnetic devices.…”
Section: Thermotropic Lcs Based On Coordination Bondsmentioning
confidence: 99%